1993
DOI: 10.1002/art.1780360915
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an interleukin‐1 receptor antagonist protein on type ii collagen–induced arthritis and antigen‐induced arthritis in mice

Abstract: Objective. To investigate the anti-arthritic effect of recombinant human interleukin-1 receptor antagonist protein (IRAP) in two experimental models of arthritis.Methods. Recombinant IRAP was administered daily to mice with type I1 collagen-induced arthritis (CIA) or with antigen-induced arthritis (AIA) provoked by methylated bovine serum albumin (mBSA). Disease incidence and severity were assessed by a clinical index and histologic features. Serum antibody to type I1 collagen, spleen cell proliferation to mBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(95 citation statements)
references
References 34 publications
(16 reference statements)
8
84
0
2
Order By: Relevance
“…Administration of human IL1Ra has been shown to inhibit the development of CIA. Although a relatively low dose of recombinant IL-1Ra (3-30 mg/day) was effective in the preventive model of murine CIA, 14 sustained high blood levels of IL-1Ra, such as by continuous administration or osmotic pumping system, were required to obtain a complete suppression of all aspects of the disease. 15,17 The efficacy of recombinant human IL-1Ra in the treatment of active RA was confirmed in long-term placebo-controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of human IL1Ra has been shown to inhibit the development of CIA. Although a relatively low dose of recombinant IL-1Ra (3-30 mg/day) was effective in the preventive model of murine CIA, 14 sustained high blood levels of IL-1Ra, such as by continuous administration or osmotic pumping system, were required to obtain a complete suppression of all aspects of the disease. 15,17 The efficacy of recombinant human IL-1Ra in the treatment of active RA was confirmed in long-term placebo-controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was already reported that repeated injections of the human IL-1Ra (hIL-1Ra) protein could induce the antibody response to hIL-1Ra in CIA mice, although the antibody response to hIL-1Ra did not inhibit the therapeutic effects of the injected protein. 14 Further investigation into the mechanism involved in the decrease in the level of transgene expression will help to develop a new strategy for long-term gene expression by naked DNA.…”
Section: Il-1ra Dna Injection Inhibits Cia J-m Kim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with rheumatoid arthritis (RA), 2 critical proinflammatory cytokines are interleukin-1 (IL-1) and tumor necrosis factor ␣ (TNF␣) (3). Inhibition of IL-1 and/or TNF␣ reduces the extent of inflammation in RA (4,5) and lessens inflammation and bone destruction in various experimental models of arthritis (6)(7)(8)(9)(10)(11)(12). Therefore, therapeutic agents that inhibit the action of these 2 cytokines are gaining rapid acceptance as early, aggressive treatments for RA.…”
mentioning
confidence: 99%
“…Animal models of arthritis have provided considerable insight into possible roles of cytokines in perpetuating and modulating arthritis. IL-1 and TNF inhibitors have been shown to ameliorate established collageninduced arthritis (49)(50)(51)(52)(53). Mice transgenic for the human TNFa gene develop chronic inflammatory arthritis, and treatment of these mice with anti-TNF MAb or rTNFR:Fc fusion protein abrogates the arthritis (5435).…”
Section: Cytokine Targetsmentioning
confidence: 99%